Adaptive wavelet packet basis selection for zerotree image coding. (2016) - Pandian, R.; Vigneswaren, T.
In this paper, we explore the possibility of wedding the adaptive wavelet packet transform with zerotree quantisation. We subject the input image to an adaptive wavelet packet decomposition, to get a full wavelet packet tree. We present a general zerotree structure for an arbitrary wavelet packet geometry in an image coding framework. Set Partitioning in Hierarchical Trees (SPIHT) and Zerotree Quantisation - Wavelet (ZQ-WV) coder are the other encoding methods. The limitations we have in these coders are that they have low performance in terms of Peak Signal-to-Noise Ratio (PSNR) and low visual quality at low bit rates.